Reproductive Performance of Garut Ewes Fed Sorghum-Indigofera after Stimulation with Pregnant Mare Serum Gonadotropin - R. Somanjaya; A. M. Fuah; S. Rahayu; L. Abdullah; M. A. Setiadi (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aimed to evaluate the effect of mixed feed sorghum-Indigofera on Garut ewes reproductive performance stimulated with Pregnant Mare Serum Gonadotropin (PMSG) hormone. Twenty-eight multiparous Garut ewes were grouped based on feed type (local forage (LF) vs. mixed feed sorghum-Indigofera (SI)), for a 30-day acclimatization period with a completely randomized design. Following acclimatization, all animals were synchronized with PGF2α (i.m.) twice, 11 days apart. Half the population of each group was stimulated with 500 IU PMSG after the second injection. Estrous characteristics were observed for seven days, followed by natural mating. Pregnancy status and the number of fetuses were detected 30 days after mating using ultrasound (USG), and reproductive efficiency was evaluated after parturition. Data during acclimatization were analyzed using a two-sample t-test, while the reproductive performances used a General Linear Model (GLM). Estrous characteristics showed no interaction (p>0.05) between feed types and PMSG stimulation. The onset of estrous in the SI treatment occurred 9.33 hours faster (p<0.05) than in the LF treatment. Meanwhile, the duration of estrous in the group stimulated with PMSG was 18.67 hours longer (p<0.05) than without PMSG. The vulva temperature at standing heat was 38.16±0.69 °C (p>0.05), with the pregnancy rate ranging 42.85%-100%. Interestingly, the SI group treated with or without PMSG had a larger litter size (1.43-4.50) compared to the LF group (1.25–1.33). It is concluded that feeding with SI had improved reproductive success, with the highest number of ewes giving birth. Additionally, the ewes fed SI with PMSG had the largest litter size.